2021
DOI: 10.21608/ejhm.2021.194053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mulligan Technique on Subacromial Impingement Syndrome: A Systematic Review

Abstract: Background: Subacromial impingement syndrome (SIS) is considered the most prevailing cause of shoulder pain. Although Mulligan's technique may be useful in treating shoulder impingement, its significance in areas of range of movement (ROM), pain, and function is still debated. Objective: To systematically review and summarize the best evidence on treating subacromial impingement syndrome using mobilization with movement. Patients and Methods: Databases Cochrane Library Web search, PEDro and PubMed were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Both groups' patient satisfaction with the course of treatment was comparable (p = 0.28). According to the findings of the study, patients with SAIS respond to both supervised exercise and mobilisation in a similar way, Ferit Pekgöz et al 18…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Both groups' patient satisfaction with the course of treatment was comparable (p = 0.28). According to the findings of the study, patients with SAIS respond to both supervised exercise and mobilisation in a similar way, Ferit Pekgöz et al 18…”
Section: Discussionmentioning
confidence: 69%
“…The overall number of people with subacromial shoulder discomfort included in this study was 358 across 11 RCTs, they compared the efficiency of MWM combined with exercise for rotator cuff mobilisation, isometric, ROM, strengthening and sham techniques. There was a non-significant difference in SPADI but a significant difference in VAS when MWM was compared to exercise, according to a meta-analysis by Mohamed Abdellatif Hassan et al (2021). 17 In another study, joint mobilisation paired with supervised exercise were examined in people with subacromial impingement syndrome (SAIS), between June 2014 and June 2015, 40 participants with SAIS for longer than six weeks were enrolled in this randomized-controlled research.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that adding MWM to supervised exercises when treating SIS patients showed a high percentage of improvement in VAS, the pain of Neer and Hawkins-Kennedy tests, and active ROM (flexion and scaption) (24,25,26,27,28) .…”
Section: Regarding Mobilization With Movementmentioning
confidence: 94%
“…It has a range of 0 to 360 and is accurate to +/-1. The validity also reliability of the electro-goniometer for measuring shoulder joint movement was tested and well documented (12,13,14) .…”
Section: -Shoulder Joint Mobilitymentioning
confidence: 99%
“…In order to accomplish this work, individuals must repeatedly lift and carry objects overhead. To perform this work efficiently, complete shoulder range of motion (ROM) and strength of the rotator cuff muscles are important components [ 14 ]. Thus, SAI has a huge impact on socioeconomic status due to an individual's working ability limitation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%